2008
DOI: 10.1007/s11242-008-9265-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-passive Transport of Volatile Organic Compounds Infiltrated from a Surface Disk Source

Abstract: An unsaturated flow and non-passive transport model for water-soluble organic compounds has been implemented in cylindrical coordinates, with a top boundary condition that accounts for different zones of the surface that can be under infiltration or volatilization independently. We simulated two-dimensional infiltration of aqueous mixtures of methanol from a disk source, its redistribution and volatilization in both homogeneous and heterogeneous soils. Simulations showed that the incoming composition significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Dispersion in solute is important in case of contaminant transport in both saturated and unsaturated soil [1][2][3], as well as nutrient transport in the root zone [4]. Gas phase dispersion…”
Section: Introductionmentioning
confidence: 99%
“…Dispersion in solute is important in case of contaminant transport in both saturated and unsaturated soil [1][2][3], as well as nutrient transport in the root zone [4]. Gas phase dispersion…”
Section: Introductionmentioning
confidence: 99%
“…Solute dispersion is important for contaminant transport in both saturated (groundwater) and unsaturated soil (Thomson, 1997;Silva, 2009;Lewis, 2010), and root zone nutrient transport (Parkinson, 2000). Gas dispersion is important in processes such as radon migration into buildings (Wang, 2002), soil aeration and movement of volatile contaminants at contaminated soil sites (Arands, 1997;Atteia, 2010) and migration and emission of CH 4 at landfills and wetlands (El-Fadel, 1997;De Visscher, 1999;Liang, 2000;Pangala, 2010;Pennock, 2010;Schaufler, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the volumetric water content and the concentration profiles together with the volatilization and evaporation fluxes were highly affected by the methanol concentration. A similar model was developed by Silva and Grifoll (2009) to simulate infiltration, redistribution, and volatilization of aqueous mixtures of methanol from a disk source.…”
Section: Introductionmentioning
confidence: 99%